Development of a metalloproteomic approach to analyse the response of Arabidopsis cells to uranium stress. Issue 8 (22nd June 2020) - Sarthou, Manon C. M.; Revel, Benoît H.; Villiers, Florent; Alban, Claude; Bonnot, Titouan; Gigarel, Océane; Boisson, Anne-Marie; Ravanel, Stéphane; Bourguignon, Jacques
Abstract : Elaboration of a top-down proteomic, biochemical and ionoproteomic toolbox to gain insights into the impact of uranyl (U) on Arabidopsis cells. Abstract : Uranium is a naturally occurring radionuclide that is absorbed by plants and interferes with many aspects of their physiology and development. In this study, we used an ionomic, metalloproteomic, and biochemical approach to gain insights into the impact of uranyl ions on the proteome of Arabidopsis thaliana cells. First, we showed that most of the U was trapped in the cell wall and only a small amount of the radionuclide was found in the cell-soluble fraction. Also, the homeostasis of several essential elements was significantly modified in the cells challenged with U. Second, the soluble proteome from Arabidopsis cells was fractionated into 10 subproteomes using anion-exchange chromatography. Proteomic analyses identified 3676 proteins in the different subproteomes and the metal-binding proteins were profiled using inductively coupled plasma mass spectrometry. Uranium was detected in several chromatographic fractions, indicating for the first time that several pools of Arabidopsis proteins are capable of binding the uranyl ion in vivo . Third, we showed that the pattern of some lysine and arginine methylated proteins was modified following exposure to U. We further identified that the ribosomal protein RPS10C was dimethylated at two arginine residues in response to uranyl ion stress. Together, these results provide the first clues for the impact of U on the Arabidopsis proteome and pave the way for the future identification of U-binding proteins.